Penyesuaian Konsep Matematika dengan Perkembangan Kognitif Anak Usia Dini - Pratiwi, Hardiyanti Ali; Yarliani, Ikta; Ageng, Diyah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This article examines how early mathematical concepts that fit the early childhood cognitive development. The introduction of early mathematical concepts becomes important for early childhood to provide various stimuli and foster childrens love of mathematics. The introduction of mathematics is not just about numeracy and formulas, but more important is the cultivation of the concept of mathematics. If early childhood has known let alone understand the concept of mathematics well, will certainly have a positive impact on subsequent developments. There are three points in this article related to early mathematical concepts that need to be introduced for early childhood: (1) matching and discriminating, comparing and contrasting, (2) classifying, sorting and grouping, (3) ordering, sequence and seriesation.